Sociology - MACIONIS, John J (New Jersey : Prentice Hall, 1999)
Suitable for one-quarter/semester or two semester introductory Sociology courses, this book shows students that sociology is relevant to their daily lives.
Includes bibliographical references and index
Keywords: Sociology, Methodology Knowledge, Sociology of Ideology